Strategi Pemasaran STP (Segmenting, Targeting, and Positioning) Sepeda Motor Yamaha NMAX di Indonesia - Jamira, Anaseputri; Iskandar, Fadil (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the Segmenting, Targeting, and Positioning (STP) Marketing Strategy of the Nmax Automatic Motorcycle produced by Yamaha. To study the Segmenting, Targeting, and Positioning of the Yamaha Nmax Automatic Motorcycle, a descriptive approach is used that describes the implementation of the STP. The types of data used include primary and secondary data. The data that has been collected is then analyzed using a qualitative approach, which involves comparison with relevant theories. The results of the study obtained show that the Yamaha Nmax Automatic Motorcycle divides the market based on demographic and psychographic variables; uses a "Full Market Coverage" targeting strategy, where many products serve many segments; and positions itself as a premium "big" automatic scooter type motorcycle in its class, which is in line with the meaning of the name, spirit, tagline echoed by the manufacturer to the minds of Indonesian consumers. The Nmax manufacturer must continue to be able to be consistent and agile in innovating, in terms of marketing strategy and the company's overall business strategy, which will optimally support and create competitive advantages in order to continue to compete and exist. The researcher only limited the research to the analysis of STP Marketing Strategy, so that more complex research involving marketing strategy and comprehensive marketing program, as well as comprehensive company strategy analysis, can be conducted to obtain more relevant and superior results.